Postextraction implant in aesthetic anterior area using the “one abutment–one time” protocol - Herrera Robayo, Marcelo (2022)
This case report presents the resolution of a common clinical situation through the installation of a post-extraction implant with the one abutment-one time protocol due to a root fracture at the cervical level of tooth #21. Materials and Methods: A 3.5 x 13 mm conical connection implant was installed using a palatal approach; concomitantly a bone xenograft was performed in the gap between the implant and the vestibular bone wall, as well as a sub epithelial connective tissue graft with the envelope technique to improve the gingival phenotype, and the fabrication of an immediate provisional tooth. Following the principle of late loading, after 6 months, the implant was rehabilitated with a definitive metal-porcelain crown. Conclusions: with the limitations of the case, it was found that this technique is safe in the medium term; it offers the advantage of resolving this type of case in a single surgical appointment, maintaining the gingival architecture and bone crestal levels.